Pharmacokinetic Interaction of Green Rooibos Extract With Atorvastatin and Metformin in Rats - Patel, Oelfah; Muller, Christo J.F.; Joubert, Elizabeth; Rosenkranz, Bernd; Taylor, Malcolm J.C.; Louw, Johan; Awortwe, Charles (Frontiers in Pharmacology, 2019)
An aspalathin-rich green rooibos extract (Afriplex GRT™) has demonstrated anti-diabetic and hypolipidemic properties, while also moderately inhibiting CYP3A4 activity, suggesting a potential for herb–drug interaction. The present study, therefore, evaluated the effects of orally administered GRT on the pharmacokinetics of atorvastatin and metformin in Wistar rats. Wistar rats were orally treated with GRT (50 mg/kg BW), atorvastatin (40 mg/kg BW) or metformin (150 mg/kg BW) alone or 50 mg/kg BW GRT in combination with 40 mg/kg BW atorvastatin or 150 mg/kg BW metformin. Blood samples were collected at 0, 10, and 30 min and 1, 2, 4, 6, and 8 h and plasma samples obtained for Liquid chromatography-mass spectrometry (LC-MS/MS) analyses. Non-compartment and two-compartment pharmacokinetic parameters of atorvastatin and metformin in the presence or absence of GRT were determined by PKSolver version 2.0 software. Membrane transporter proteins, ATP-binding cassette sub-family C member 2 (Abcc2), solute carrier organic anion transporter family, member 1b2 (Slco1b2), ATP-binding cassette, sub-family B (MDR/TAP), member 1A (Abcb1a), and organic cation transporter 1 (Oct1) mRNA expression were determined using real-time PCR expression data normalized to β-actin and hypoxanthine-guanine phosphoribosyltransferase (HPRT), respectively. Co-administration of GRT with atorvastatin substantially increased the maximum plasma concentration (Cmax) and area of the plasma concentration–time curve (AUC0-8) of atorvastatin by 5.8-fold (p = 0.03) and 5.9-fold (p = 0.02), respectively. GRT had no effect on the plasma levels of metformin. GRT increased Abcc2 expression and metformin downregulated Abcb1a expression while the combination of GRT with atorvastatin or metformin did not significantly alter the expression of Slco1b1 or Oct1 did not significantly alter the expression of Sclo1b2 or Oct1. Co-administration of GRT with atorvastatin in rats may lead to higher plasma concentrations and, therefore, to an increase of the exposure to atorvastatin.